Redirecting immunity via covalently incorporated immunogenic sialic acid on the tumor cell surface. Issue 6 (1st March 2016) - Lin, Bijuan; Wu, Xuanjun; Zhao, Hu; Tian, Yunpeng; Han, Jiahuai; Liu, Jian; Han, Shoufa
Abstract : Anti-tumor immunity was achieved via metabolically incorporated non-self antigen-labelled sialic acid on the tumor surface glycocalyx. Abstract : Techniques eliciting anti-tumor immunity are of interest for immunotherapy. We herein report the covalent incorporation of a non-self immunogen into the tumor glycocalyx by metabolic oligosaccharide engineering with 2, 4-dinitrophenylated sialic acid ( DNP Sia). This enables marked suppression of pulmonary metastasis and subcutaneous tumor growth of B16F10 melanoma cells in mice preimmunized to produce anti-DNP antibodies. Located on the exterior glycocalyx, DNP Sia is well-positioned to recruit antibodies. Given the high levels of natural anti-DNP antibodies in humans and ubiquitous sialylation across many cancers, DNP Sia offers a simplified route to redirect immunity against diverse tumors without recourse to preimmunization.